Probing Interfacial Surface State Excitons in Nanoscale Synthesized CuxS/MoS2 Heterostructure. Issue 6 (28th January 2019) - Shahzad, Rauf; Mun, Jihun; Kim, Tae Wan; Kang, Sang‐Woo
Abstract: Two dimensional (2D) layer integration of different materials facilitates new functionalities in material engineering to produce novel structures with specialized properties. Fabrication of large‐scale 2D heterostructure with atomically clean interface, and unveiling the distinct interlayer transition, is a challenging process. In this paper, the vertical heterostructure of copper sulfide (Cu x S) and molybdenum disulfide (MoS2 ) nanosheets is synthesized by sulfurization of pre‐deposited metal films. Optical bandgap transition and phonon vibration frequency are observed in the heterojunction area with respect to individual nanosheets. Raman shift in phonon vibration modes of MoS2 shows the interlayer coupling effect. Photoluminescence (PL) intensity of monolayer MoS2 is quenched due to bandgap offset interlayer transition. Bandgap alignment of Cu x S (1 < x < 2) with MoS2 is a tunable staggered symmetry that yields charge transfer at the heterostructure interface. Photoexcited electron–hole pairs are moving across the interface much faster than recombining into the intralayer excitons. The synthesized Cu x S/MoS2 heterostructure is well defined over a large area, with controllable thickness and a scalable position. Heterostructure has great potential for future device applications in optoelectronics based on optical excitonic response and charge carrier dynamics. Abstract : Predefined vertical heterostructure of copper sulfide and molybdenum disulfide Cu x S/MoS2 nanosheets is synthesized by physical vapor deposition. Heterostructure with staggered bandgap symmetry revealed strong charge transfer interlayer coupling. Photoluminescence intensity of monolayer MoS2 in heterojunction area is quenched due to the bandgap offset interlayer transition. Specially separated intralayer excitons are transferred to low‐energy states by interlayer relaxation and radiative recombination.